Pengaruh Perbedaan Perasan Dan Ekstrak Kulit Pisang Mas (Musa Acuminata Colla) Terhadap Kadar Vitamin C Dengan Metode Spektrofotometri Uv- Vis - Andriana, Azizah Huda; Susanti, Maria Mita (Unit Penelitian dan Pengabdian Masyarakat Politeknik Kesehatan Bhakti Mulial, 2024)
Banana is a type of plant that is abundant in Indonesia, but the utilization of waste peels has not been done optimally. The peel of the golden banana (Musa acuminata Colla) contains vitamin C. It is necessary to pay attention to the processing of the peel of the golden banana because vitamin C is easily oxidized by heat, light and metals. This study aims to determine the effect of banana peel filtrate and extract on vitamin C levels. This type of research is experimental. The independent variables were the filtrate and golden banana peel extract with the dependent variable namely the organoleptic levels of vitamin C in the filtrate and golden banana peel extract. The test was carried out qualitatively with Benedict's reagent, FeSO4 & NaOH and quantitatively using UV-Vis spectrophotometry with a wavelength of 265 nm. The results of measuring vitamin C levels were analyzed using SPSS with the Independent T-Test test. The qualitative test results showed that the filtrate and banana peel extract positively contained vitamin C. The level of vitamin C in the filtrate was 0.1538918% w/w (153.892 mg/100 g) while in the extract it was 0.1065812% w/w (106.581 mg/w 100g). Based on the results of analysis of mas banana peel filtrate and mas banana peel extract, it has an effect on Vitamin C levels with a p value <0.05